THE INFLUENCE OF INNOVATION CAPACITY ON THE PERFORMANCE OF MSMES IN GORONTALO MEDIATED BY THE BUSINESS ENVIRONMENT - Djou, Sitti Husna Noviana; Husain, Putra Arisandi; Lukum, Marlon Mohamad Lukum; Ente, Moh Nur Hafis (LP2M Universitas Bina Mandiri Gorontalo, 2025)
The rapid growth of MSMEs in Indonesia continues to face serious challenges in terms of competitiveness and business sustainability, especially amid global economic pressure and market uncertainty. One strategy believed to improve MSME performance is by strengthening innovation capacity. However, in practice, the influence of innovation capacity on business performance does not occur directly, but is significantly mediated by the business environment. This study employed a quantitative approach using SEM-PLS on 73 MSME respondents and found that innovation capacity has a positive and significant effect on MSME performance when mediated by the business environment (t-statistic = 5.232; p < 0.001). The findings highlight that innovations undertaken by MSMEs become more effective and impactful when supported by a favorable business ecosystem, including market access, regulatory policies, partnerships, and infrastructure. This study enriches the literature on innovation management in MSMEs and provides practical implications for policymakers and stakeholders to build a supportive business environment that enables innovation as a pathway to enhance performance